Das Mechanische Corps. : Auf den Spuren von Jules Verne. - Lang, Peter; Tannert, Christoph; LeVitte Harten, Doreet; de Ruyter, Thibaut (Berlin : Künstlerhaus Bethanien Gmbh, 2014)
Akai, Yoshi ; Atak ; Boden, Roland ; Bouvet, Jean-Pierre ; Capper, James ; Castillo, Wendy Esmeralda ; Fahrnländer, Stefan ; Freitas, Eric ; Fuhrmann, Roland ; Gerth, Andreas ; Hildebrandt, Gregor ; Janke, Karl Hans ; Kellner, Thomas ; Kim, Yunchul ; Kwade, Alicja ; Van Lankveld, Gerard ; Lewanowsky, Via ; Mertens, Florian ; Mesmer, Gustav ; Moebius ; 'Doc' Nagy, Richard ; Nowak, Nik ; Ong, Donna ; Panamarenko ; Sailstorfer, Michael ; Schlesier-Steampunker, Alexander ; Shrat, Henrik ; Schuiten, François ; Scrivener, Amanda ; Steam Noir - Klinke, Verena & Mertikat, Felix ; Suekichi, Haruo ; Topolovac, Philip ; Vandenbroucke, Brecht ; Viron Erol Vert ; de Vink, Jos ; Watabe, Takashi ; Wrede, Brecht ; Ziervogel, Ralf.
Tentoonstelling 'Das Mechanische Corps. Auf den Spuren von Jules Verne', Künstlerhaus Bethanien, Berlin, 06.06.2014 - 03.08.2014.
Duits
Engels
Frans
boek